Effect of GIC neutral blocking devices (NBDs) on power network ferroresonance in Malaysia - Mohammed Khurshid, Zmnako; Ab Aziz, Nur Fadilah; Rhazali, Zeti Akma; Ab Kadir, Mohd Zainal Abidin (IEEE Access, 2022)
Geomagnetic disturbance (GMD) arises during space weather and solar activity can result in geomagnetically induced current (GIC) flow in the grounded power transformers in the power network. This GIC may cause half-cycle saturation of transformers and lead to severe damage or blackout. To block the GIC flow into the power transformers, the neutral blocking devices (NBDs) based on capacitor banks are often installed in the neutral ground paths of transformers to mitigate the GIC. However, the high voltage (HV) can build up across these capacitors during ground faults and may cause a ferroresonance phenomenon in the power network. This phenomenon generates high voltages/currents in the transformer windings and results in transformer failure. This work investigates the effect of connected NBDs to the power transformers on the potential power network ferroresonance in Peninsular Malaysia. The complete analysis was carried out using the Power System Computer-Aided Design for Electromagnetic Transients including Direct Current (PSCAD/EMTDC) software. These transformers were selected in the power network due to the sensitivity of their locations to GMD events. The NBD systems were tested under different working conditions. The simulation results found that the metal oxide varistors (MOVs) arresters in NBDs fault protection mode effectively clamped ferroresonance overvoltages below the protection level under faulty conditions. Also, the results showed that GIC protection modes with 1 Ω and 3180 µF in the mitigation systems had the lowest ferroresonance overvoltages in the neutrals of the transformers under faulty conditions. Based on the results, the recommendations were provided to the local power utility which will help to improve the reliability of the power supply to the consumers.